Cognitive-behavioral screening reveals prevalent impairment in a large multicenter ALS cohort. (1st March 2016) - Murphy, Jennifer; Factor-Litvak, Pam; Goetz, Raymond; Lomen-Hoerth, Catherine; Nagy, Peter L.; Hupf, Jonathan; Singleton, Jessica; Woolley, Susan; Andrews, Howard; Heitzman, Daragh; Bedlack, Richard S.; Katz, Jonathan S.; et al.
Abstract : Objectives: To characterize the prevalence of cognitive and behavioral symptoms using a cognitive/behavioral screening battery in a large prospective multicenter study of amyotrophic lateral sclerosis (ALS). Methods: Two hundred seventy-four patients with ALS completed 2 validated cognitive screening tests and 2 validated behavioral interviews with accompanying caregivers. We examined the associations between cognitive and behavioral performance, demographic and clinical data, and C9orf72 mutation data. Results: Based on the ALS Cognitive Behavioral Screen cognitive score, 6.5% of the sample scored below the cutoff score for frontotemporal lobar dementia, 54.2% scored in a range consistent with ALS with mild cognitive impairment, and 39.2% scored in the normal range. The ALS Cognitive Behavioral Screen behavioral subscale identified 16.5% of the sample scoring below the dementia cutoff score, with an additional 14.1% scoring in the ALS behavioral impairment range, and 69.4% scoring in the normal range. Conclusions: This investigation revealed high levels of cognitive and behavioral impairment in patients with ALS within 18 months of symptom onset, comparable to prior investigations. This investigation illustrates the successful use and scientific value of adding a cognitive-behavioral screening tool in studies of motor neuron diseases, to provide neurologists with an efficient method to measure these common deficits and to understand how they relate to key clinical variables, when extensive neuropsychological examinations are unavailable. These tools, developed specifically for patients with motor impairment, may be particularly useful in patient populations with multiple sclerosis and Parkinson disease, who are known to have comorbid cognitive decline.